Effect of Addition of Moringa Leaves (Moringa oleifera) on Chemical Characteristics and Nutritional Value of Chicken Sausage Chips - F. Lindasari; P. R. Kale; D. Darmakusuma (Universitas Bengkulu, 2021)
The leading cause of malnutrition in NTT province is the lack of balanced nutrition, one of which is macronutrients such as carbohydrates, proteins, and fats. So, there is a need for innovation from livestock products rich in readily available animal protein, one of which is chicken. Utilization of the results of heating technology Moringa leaf flour which is rich in micro and macronutrients is available in the province of NTT, so that it can provide processed products in the form of chicken sausage chips with the addition of Moringa leaf flour. This study aims to determine the effect of adding Moringa leaf flour P0, P1, P2, and P3 on chicken sausage chips' chemical characteristics and nutritional value. Each treatment P0 Moringa leaf flour (0%), P1 Moringa leaf flour (1%), P2 Moringa leaf flour (2%), P3 Moringa leaf flour (3%). The experimental method used is a simple, completely randomized design (CRD) with four treatments and four replications. Analysis of the ANOVA (Analysis of Variance) data and Duncan's further test, while the nutritional value content was calculated according to BPOM regulation NO 19 of 2019 concerning Nutrition Label Reference. The results showed that the addition of Moringa leaf flour had a significant effect on the chemical characteristics of P<0.05. According to the National Food and Drug Administration Agency (BPOM), for appropriate nutritional content, information on the nutritional value of chicken sausage chips.